Molecular motion in the nanospace of MOFs upon gas adsorption investigated by in situ Raman spectroscopy. (27th October 2020) - Kusaka, Shinpei; Nakajima, Yasuaki; Hori, Akihiro; Yonezu, Akira; Kikushima, Kenta; Kosaka, Wataru; Ma, Yunsheng; Matsuda, Ryotaro
Abstract : Molecular motions taking place in the nanospace of metal–organic frameworks (MOFs) are an interesting research subject, although not yet fully investigated. Abstract : Molecular motions taking place in the nanospace of metal–organic frameworks (MOFs) are an interesting research subject, although not yet fully investigated. In this work, we utilized in situ Raman spectroscopy in the ultralow-frequency region to investigate the libration motion (including the rotational motion of phenylene rings) of MOFs, in particular [Cu2 (bdc)2 (dabco)] (Cu-JAST-1), where bdc = 1, 4-benzenedicarboxylate and dabco = 1, 4-diazabicyclo[2.2.2]octane. The libration mode of Cu-JAST-1 was found to be significantly suppressed by the adsorption of various guest molecules, such as CO2, Ar, and N2 . In addition, an appreciable correlation between the libration mode and adsorption equilibrium time was identified, which provides useful novel tools in the design of MOFs acting as molecular adsorption and separation materials.